Analysis of Educational Messages in The Lion King Movie: Perspectives on Character Education and Environmental Conservation - Enos Lolang; Rinovian Rais; Adolfina Oualeng; Mustofa Aji Prayitno (COMPETITIVE: Journal of Education, 2023)
This study aims to analyze the educational messages related to character education and environmental conservation in the film The Lion King (1994). Using a qualitative research design and content analysis, the film's narrative structure, dialogue, and visual elements were analyzed to identify key themes and sub-themes related to character education and environmental conservation. The results reveal that The Lion King contains important educational messages related to responsibility, leadership, respect for nature, and the interconnectedness of all living things. These findings highlight the potential of films as a tool for promoting positive values and education. The study's implications for education and media literacy are discussed, emphasizing the importance of incorporating media into educational curricula to enhance students' understanding of important concepts and foster critical thinking and analysis skills. Overall, this study shows that films, such as The Lion King, can be a valuable tool for promoting positive values and education, especially for character education and environmental conservation. The findings suggest that educators can use media content analysis as a means to identify and analyze the educational messages embedded in films, and incorporate these messages into educational curricula to enhance students' learning and development.